Diseño e implementación de un dispositivo electrónico para la cuantificación de temperatura, luminosidad, ph y humedad para la producción agrícola en la carrera de Agronomía en la Universidad Técnica de Cotopaxi - Sivinta Almachi, Luis Octavio (2023)
The technological proposal arises from the need for an electronic device to quantify the "temperature, humidity, luminosity and pH", which agricultural development needs, the acquisition and observation of these parameters allows to determine changes due to various factors in the place of implementation, The main objective is to design and implement a prototype using an Arduino "Mega2560" card and the App Inventor software for the observation of data produced in the greenhouse in the Agronomy Career of the Technical University of Cotopaxi. Bearing in mind the characteristics, the electronic device was designed through the quantitative and experimental methodology, which determine the technical specifications, the machine processes the information provided by the sensors for display on a Nextion screen, for data interpretation the graphic device each one of these based on time and with the mobile application through a Bluetooth module you can view the data and graphs on the cell phone, resulting in the temperature with the lowest value being 11.7°C at night and higher than 23 °C in the afternoon, luminosity with the lowest value of 298 Ix and higher than 651 1x must receive a minimum of 6 hours of light, humidity with the lowest value of 72% and higher than 100 due to the goal irrigation system and the pll with the lowest value of 6.81 and the highest of 7.05 affected by water.